Paradigma Kalam Dalam Konservasi Lingkungan Menurut Said Nursi - Nur Hadi Ihsan; Moh. Isom Mudin (Universitas Darussalam Gontor, 2020)
This research departs from the fact that environmental conservation efforts are increasingly needed due to natural damage that increases continually. However, the instrumental and social efforts performed by the environmental activists are still partial and have not touched the fundamental aspects. Islam as a Religion and basis of comprehensive science could resolve this aspect. Rasa’il Nur, a masterpiece written by Sa’id Nursi supposed to offers a solution to the problem. This study aims to reveal the environmental conservation paradigm by Sa'id Nursi and find a new direction based on Islamic environmental conservation. This research is a literature study, qualitative models and figure studies, using critical-reflective analysis, with a kalam perspective. Nursi views the strong relationship of Tauhid (monotheism) and nature. Tauhid (monotheism) is the principle understanding to see the ecological elements which he calls the